Identification of mental models about cooling systems of students in the technical course in automotive maintenance (Research, Society and Development, 2020)
This study has as main objective to identify the evolution of mental models on the knowledge of students of the Technical Course in Automotive Maintenance Integrated to High School, on the cooling systems of the internal combustion engines of the Otto and Diesel cycles. For such, a questionnaire was developed about the subject addressed. Five questions were prepared initially, that is, before the student had contact in the classroom with the subject addressed in this research. These questions were classified into three levels, which was easy, medium and difficult. After the content was administered, another questionnaire was applied containing five other questions, these were also classified into three levels of difficulty for the verification of the new scenario on the identification of students' mental models. The result of the first questionnaire was the finding that the students 'mental models are significantly heterogeneous and the use of the questionnaires before and after the subject was shown to be efficient in diagnosing the maturity and the evolution of the students' mental models.